Speech Act Analysis in Indonesian: A Case Study of Buying and Selling Transactions at Gelugur Market, Rantauprapat - Anisa Damayanti; Patmalia Dalimunthe; Rini Andriani Munthe; Saprida; Juli Yani; Astari Rara Dandi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study investigates the speech acts present in buying and selling transactions at Gelugur Market, Rantauprapat, with a focus on how sellers and buyers utilize language to achieve their communication goals. The research examines the forms of illocutionary acts used in these interactions and their roles in facilitating effective transactions. Employing a qualitative descriptive approach, this field study was conducted from August to September 2024. Data were collected using a combination of observation, recording, interviews, and the listen-and-note technique to ensure comprehensive analysis. The results indicate the presence of five primary types of speech acts in the transactional interactions: (1) assertive acts, which convey the speaker’s beliefs or statements of truth, such as product descriptions or price confirmations; (2) directive acts, where speakers attempt to influence the actions of others, such as requesting, advising, or persuading; (3) commissive acts, involving promises or commitments by sellers or buyers, such as agreeing to a price or a delivery time; (4) declarative acts, where speakers make statements that bring about immediate changes in the transaction, such as closing a deal; and (5) expressive acts, which reflect the speakers' emotions or attitudes, such as gratitude or apologies during the negotiation. This study provides a deeper understanding of the communicative strategies used by sellers and buyers in Gelugur Market and highlights the cultural and social factors that influence their interactions.